Optimal operation of combined cooling heat and power (CCHP) systems in future energy networks - Goo, Yong Kiat (2019)
Traditional power plants produce electrical power and convert electrical power to heat and cooling power. As such, with the rapid development and evolution of technology in the modern world, demands for energy in the form of electrical power, as well as cooling and heat power, will increase. Hence, CCHP-based microgrid is been widely focus in the current market. Therefore, the purpose of this report is to investigate the most economical mode of CCHP microgrid application in the energy network by using the graphical results to compare the reduction of total cost for consumer in 2 separated mode in microgrid to determine the most cost-effective mode. The presented method in this report can reduce the operation cost of the CCHP-based microgrid without bringing any disturbance to the consumer and increase the usage of clean energy effectively. High level programming MATLAB and YALMIP will be used to find out the most economical mode of usage in microgrid, the result in the report would effectively reduce on the total cost of microgrid in certain mode.